2014
DOI: 10.1139/bcb-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the adipogenesis in intramuscular and subcutaneous adipocytes from Bamei and Landrace pigs

Abstract: Fat deposition is a complex process involving proliferation, differentiation, and lipogenesis of adipocytes. Bamei and Landrace are considered to represent fat- and lean-type pig breeds. Subcutaneous (SC) and intramuscular (IM) pre-adipocytes were cultured to compare the proliferation and lipogenesis in these breeds. The differentiated adipocytes were exposed to glucose or insulin to evaluate their effects on lipogenesis and lipogenic gene expression. Pre-adipocytes proliferated dramatically faster in SC vs. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 53 publications
3
36
0
Order By: Relevance
“…Primary cultures of preadipocytes were isolated as previously described (Zhang et al, 2014). Cells were seeded in 25-cm culture flask and maintained in basal medium, DMEM/F12 medium (GIBCO/BRL, USA) supplemented 10% fetal bovine serum (FBS, ScienCell, USA), at 37°C in humidified atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Primary cultures of preadipocytes were isolated as previously described (Zhang et al, 2014). Cells were seeded in 25-cm culture flask and maintained in basal medium, DMEM/F12 medium (GIBCO/BRL, USA) supplemented 10% fetal bovine serum (FBS, ScienCell, USA), at 37°C in humidified atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Fat deposition is a complex process related to lipogenesis, adipocyte proliferation and differentiation. Previous research showed that the proliferation, differentiation and lipogenesis capability of preadipocytes was stronger in Bamei (fat-type) pig than in Landrace (lean-type) pig [13]. The intramuscular fat content in Erhualian pig (fattype) was remarkably different at different growth stages, whereas that in Large White pig changed little during growth [15].…”
Section: Pigsmentioning
confidence: 99%
“…They include stearoyl-CoA desaturase (SCD) [7][8][9], fatty acid synthase (FASN) [10,11], sterol regulatory element binding transcription factor 1 (SREBF1) [10], peroxisome proliferator-activated receptor γ (PPARγ) [12]. Some molecular events in the development of intramuscular fat have been recently revealed using longissimus dorsi muscle or adipocytes in pig [11,[13][14][15]. These studies indicate that adipocyte proliferation and differentiation is higher in subcutaneous fat than in intramuscular fat as well as in fat-type pig than in lean-type pig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers for genes important for insulin responsiveness of adipose tissue were also examined and included sterol regulatory element-binding protein 1 (SREBP), carbohydrate regulatory element-binding protein (ChREBP) and insulin receptor substrate 1 (IRS1). Primers for SREBP were obtained from Gondret et al (2011), whereas primers for ChREBP were acquired from Zhang et al (2014). IRS1 primers were derived from Jiao et al (2011).…”
Section: Agp and Lipogenesis In Neonatal Pigsmentioning
confidence: 99%